Cell cycle-dependent nuclear retention of p53 by E2F1 requires phosphorylation of p53 at Ser315. - Fogal, V; Hsieh, J; Royer, C; Zhong, S; Lu, X (2005)
We show here that the cell cycle-dependent DNA-binding and transcriptional activity of p53 correlates with E2F expression in human primary fibroblasts. E2F1 binds and stimulates DNA-binding, transactivation and apoptotic functions of p53 but not p63 and p73. E2F1 binds residues 347-370 of p53 and enhances nuclear retention of Ser315 phosphorylated p53. This regulation of p53 by E2F1 is cell cycle dependent, as the cellular distribution of Ser315 phosphorylated p53 is associated with the periodic expression of E2F and cyclin A throughout the cell cycle. This is the first demonstration that the activities of p53 are regulated during the cell cycle by E2F/p53 interactions and that phosphorylation of p53 at Ser315 is required for this regulation.